Treatment of patients with multiple myeloma who are eligible for stem cell transplantation: position statement of the Myeloma Foundation of Australia Medical and Scientific Advisory Group. Issue 1 (January 2015) - Quach, H.; Joshua, D.; Ho, J.; Szer, J.; Spencer, A.; Harrison, S. J.; Mollee, P.; Roberts, A. W.; Horvath, N.; Talulikar, D.; To, B.; Zannettino, A.; et al.
Abstract The survival of patients with multiple myeloma (MM) has improved substantially since the introduction in the late 1980s of high‐dose chemotherapy (HDT) supported by autologous stem cell transplantation (ASCT). Further improvements have been observed following the availability of immunomodulatory drugs (IMiD) such as thalidomide and lenalidomide, and the proteasome inhibitor, bortezomib. Here, we summarise the recommendations of the Medical Scientific Advisory Group to the Myeloma Foundation of Australia for patients considered suitable for HDT + ASCT as part of initial therapy. These recommendations incorporate the various phases of treatment: induction, HDT conditioning and maintenance therapy.